The Relationship Between Self-Efficacy and Hardiness on Career Adaptability Among Eleventh-Grade Students at Muhammadiyah Vocational High School Ciledug, Cirebon - Andini, Rizky Dwi; Saraswati, Sinta (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims toexaminethe relationship between self-efficacy and hardiness on the career adaptability of eleventh-grade students at SMK Muhammadiyah Ciledug, Cirebon.Aquantitative approach with a correlationaldesign was employed.A sample of 121 students wasselected using aproportionate random sampling technique from a population of 173 students. Datawere collectedthrough interviews, surveys, and validated psychological scales. Data analysisincludednormality tests, descriptivestatistics,and Pearsoncorrelation, conducted usingSPSS version 26. The resultsindicatedthatstudents' levelsof self-efficacy, hardiness, and career adaptability weremoderate.The correlationanalysis revealeda very strong relationship between self-efficacy and career adaptability(r=0.909)and a moderate relationship between hardiness and career adaptability(r= 0.051). The studyconcludesthat bothself-efficacy and hardiness contribute to students' career adaptability, with self-efficacyexertinga stronger influence. Therefore,enhancingthese factors through appropriate guidance and counselingservices is essentialto betterprepare students for theworkforce.